1991
DOI: 10.1111/j.1365-246x.1991.tb03455.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetostratigraphy of the Miocene-Pleistocene Surai Khola Siwaliks in West Nepal

Abstract: S U M M A R YMagnetostratigraphic age dating has been carried out on sandstones of a wellexposed continuous 5500 m thick Miocene-Pleistocene section in the Surai Khola area (West Nepal). The section is situated in the Siwalik Range which consists of molasse sediments from the Himalaya. Progressive demagnetization and isothermal remanence experiments prove that haematite is the carrier of the characteristic remanent magnetization (ChRM) throughout the entire section. The final polarity sequence is based on 436 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
106
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(122 citation statements)
references
References 7 publications
11
106
1
Order By: Relevance
“…The experiments conducted are: NRM measurements with stepwise alternating field demagnetization (AFD: up to 150 mT) and thermal demagnetization (ThD: up to 700C), measurements of the initial magnetic susceptibility and its changes during stepwise heating, isothermal remanent magnetization (IRM) acquisition and demagnetization, and study of opaque minerals in polished thin sections (Appel et al 1991, Gautam and Appel 1994, and Rösler et al, 1997. Figure 5 shows the NRM data plotted against magnetic susceptibility for 3 sections.…”
Section: Magnetization Properties Of Siwalik Sediments In Nepal: a Sumentioning
confidence: 99%
See 2 more Smart Citations
“…The experiments conducted are: NRM measurements with stepwise alternating field demagnetization (AFD: up to 150 mT) and thermal demagnetization (ThD: up to 700C), measurements of the initial magnetic susceptibility and its changes during stepwise heating, isothermal remanent magnetization (IRM) acquisition and demagnetization, and study of opaque minerals in polished thin sections (Appel et al 1991, Gautam and Appel 1994, and Rösler et al, 1997. Figure 5 shows the NRM data plotted against magnetic susceptibility for 3 sections.…”
Section: Magnetization Properties Of Siwalik Sediments In Nepal: a Sumentioning
confidence: 99%
“…Data from the four sections belonging to this area are treated in detail in Appel et al (1991), Rösler et al (1997) and Rösler (1998). The sections are briefly described here.…”
Section: Magnetic Polarity Sequences and Depositional Chronologymentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of lithological character she divided the stratigraphy of the Siwalik Group along the Surai Khola section into fi ve units namely the Bankas Formation, Chor Khola Formation, Surai Khola Formation, Dobatta Formation and Dhan Khola Formation. Palaeomagnetic dating of the Surai Khola sequence indicated a time scale from 13 to 1 Ma (Appel et al 1991, Appel andRoesler 1994 (West et al1991). …”
Section: The Siwalikmentioning
confidence: 99%
“…During the last two decades, it has been demonstrated that the chronology of the Mio-Pliocene fluvial sediments of the Siwalik Group from Pakistan, India and Nepal can be deciphered through correlation of magnetic polarity reversal patterns to the geomagnetic polarity time scale (GPTS) (Barndt et al, 1978;Opdyke et al, 1979;Tauxe and Opdyke, 1982;Johnson et al, 1982Johnson et al, , 1983Tokuoka et al, 1986;Ranga Rao et al, 1988;Opdyke, 1990;Appel et al, 1991;Harrison et al, 1993;Gautam and Appel, 1994;Burbank et al, 1996;Rösler et al, 1997). These data are invaluable for regional chronological correlation throughout the Sub-Himalayan belt.…”
Section: Introductionmentioning
confidence: 99%